2013
DOI: 10.2215/cjn.03680412
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Cyclophosphamide and Plasmapheresis in Dialysis-Dependent ANCA-Associated Vasculitis

Abstract: Study (EUVAS) investigators SummaryBackground and objectives Induction therapy with oral cyclophosphamide (CYP) has been a mainstay of treatment in patients with severe renal failure secondary to ANCA-associated vasculitis (AAV). Recent evidence proposes using pulsed intravenous CYP in less severe disease to minimize adverse events. It is unclear if this can be translated to those with dialysis-dependent renal insufficiency.Design, setting, participants, & methods All AAV patients presenting between 2005 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 19 publications
7
28
1
3
Order By: Relevance
“…Numbers of patients in each of the treatment groups were small and only 46 patients were treated with oral cyclophosphamide (7 patients received no treatment), compared with a total of 110 patients aged >65 years in our cohort [13]. In multivariate analysis, increasing age was a significant predictor of survival as seen in our cohort; however, dialysis-dependence was not, in contrast to our findings and other studies [1,4,7,13]. The follow-up time in the study was relatively short (2 years) and the wide-ranging effects of immunosuppressive treatment in the elderly such as risk of infections, leukopenia and relapse were not assessed, which as we have shown, contribute to significant morbidity and mortality in this population.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Numbers of patients in each of the treatment groups were small and only 46 patients were treated with oral cyclophosphamide (7 patients received no treatment), compared with a total of 110 patients aged >65 years in our cohort [13]. In multivariate analysis, increasing age was a significant predictor of survival as seen in our cohort; however, dialysis-dependence was not, in contrast to our findings and other studies [1,4,7,13]. The follow-up time in the study was relatively short (2 years) and the wide-ranging effects of immunosuppressive treatment in the elderly such as risk of infections, leukopenia and relapse were not assessed, which as we have shown, contribute to significant morbidity and mortality in this population.…”
Section: Discussioncontrasting
confidence: 81%
“…Despite a greater total immunosuppression burden in younger patients, they were more likely to relapse than older patients (p = 0.004). This may relate to PR3-positivity, which is a major prognostic factor for relapse in AAV as well as renal survival in long-term follow-up [3,7,19,20,21,22]. PR3-positivity and age appear to be independent predictors of a poorer outcome in AAV [8,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, pulsed CYC has become increasingly used in the induction treatment in generalized AAV [27]. Later, Pepper et al [28] have shown that intravenous CYC (in combination with plasma exchange) may be successfully used even in the treatment of dialysis-dependent patients, who were excluded from the CYCLOPS Trial.…”
Section: Management and Current Treatment Of Rpgn In The Elderlymentioning
confidence: 99%
“…Благодаря этому плазмаферез активно применяется при аутоиммунных заболеваниях, таких как системная красная волчанка, ревматоидный артрит, псориаз и др. [42,[44][45][46][47].…”
Section: современные тенденции в лечении увеитовunclassified